STRATEGI KOMUNIKASI CORPORATE SOCIAL RESPONSIBILITY DALAM MENINGKATKAN CITRA PERUSAHAAN DI PT. CIREBON ELECTRIC POWER - nurul inayah; heriyani agustina; khairudin imawan (JURNAL SIGNAL, 2017)
ABSTRACT Corporate social responsibility or social responsibility has now become an essential part of running a business enterprise. The role of a Public Relations practioners in this case to determine important aspect in the successful delivery of messages to the target audience, the aims of this Research “Communicatio Strategy Corporate Social Responsibility in Improving Corporate Image PT. Cirebon Electric Power” are: (1) To know the communication strategy use to PT. Cirebon Electric Power is currently conductingCorporate Social Responsibility, (2) To know a Public Relations strategy in improving the company’s image, (3) To know the corporate image of PT. Cirebon Electric Power in the public, (4) To know any obtacles encountered in conveying the message. Researcher used qualitative research methods with descriptive approach. Researcher directly to the field, conducting interviews and acting as observers, to get the data and arguments wich are then processed through a qualitative descriptive approach. The research results show that: (1) The communication strategy for implementing Corporate Social Responsibility first PT. Cirebon Electric Power did social mapping, research study and adjust to the propriety of the EIA/ environmental management framework, consultation in the village forum, involving the village and local community leader, (2) Strategic Public Relations is done through a series of activities especially Corporate Social Responsibility, philanthropy and gathering to establish communication tehnuiques used and the use of media as a a means of wider dissemination of information, (3) With a range of CSR activities and corporate strategy which has been very well reseived and get an impression, of course assessment and positive image of the community, (4) communication barrier experienced by PT. Cirebon Electric Power, among the negative perception the public about the impact of a power plant construction. However, these obstacles can be overcome through persuasive approach and program of CSR activities.  Keywords: Communication, Corporate Social Responsibility, Corporate Image